2005
DOI: 10.1177/0894439304271536
|View full text |Cite
|
Sign up to set email alerts
|

The Realness of Cybercheating

Abstract: This paper considers the deviant behaviour of Internet infidelity. Although a plethora of research has been conducted on offline infidelity and jealousy, to date, there has been very little written about Internet infidelity and jealousy associated with cyber-relationships. Given the potential problems that online infidelity might bring to a relationship, this area of research warrants some attention. This study drew from Kitzinger and Powell's (1995) story completion method in order to explore men and women's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(25 citation statements)
references
References 21 publications
2
15
1
7
Order By: Relevance
“…These original findings confirm the existence of "modern" forms of infidelity. While previous studies have suggested that these virtual relationships do not represent a "real" physical transgression of couple norms or a betrayal of one's partner [55], our empirical data is evidence to the contrary.…”
Section: Discussioncontrasting
confidence: 88%
“…These original findings confirm the existence of "modern" forms of infidelity. While previous studies have suggested that these virtual relationships do not represent a "real" physical transgression of couple norms or a betrayal of one's partner [55], our empirical data is evidence to the contrary.…”
Section: Discussioncontrasting
confidence: 88%
“…Online romantic relationships have been described by individuals as intimate, real, and as important as any face-to-face relationship (Merkle & Richardson, 2000). Although studies have supported the idea that engaging in online sexual conversations and sharing online emotional information are true forms of infidelity (e.g., Docan-Morgan & Docan, 2007;Underwood & Findlay, 2004;Whitty, 2003Whitty, , 2005, according to Shaw (1997), online infidelity is behaviorally different from other types of infidelity. In this context, the associated factors are yet to be well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that perhaps much of the Internet behavior by individuals is underestimated and poor, but it's betrayal when the attitude toward the opposite sex behaviors would evaluated. So one of reasons to explain why some people are involved in such relationships could be applied that their opinions and behaviors about infidelity are not their own (15,21,22).…”
Section: Discussionmentioning
confidence: 99%